Growth promoting bacteria associated with Opuntia cholla rhizosphere - Manriquez-Rivera, Gisela Alejandra; Rojas-Contreras, Maurilia; Murillo-Amador, Bernardo; Arce-Amezquita, Pablo Misael (Journal of the Professional Association for Cactus Development, 2025)
Opuntia is one of the most diverse and complex genera of the cactaceae family. This cactaceae has a wide distribution and presence in Mexico. The soil and plant microbiome, in natural ecosystems, play a crucial role on plant development under diverse conditions, impacting biodiversity across different regions. The isolation and characterization of these microorganisms allows the identification of those with agronomic potential; especially the microorganisms that act as plant growth promoters. Therefore, this study focused on the quantification and identification of bacteria with agronomic potential associated with the rhizosphere of Opuntia cholla. The samples of soil and roots were collected from different plants established at three different locations around La Paz, B.C.S., Mexico, with different soil properties (organic matter content, pH and electrical conductivity). The samples were taken at 15 cm dept, removing the soil and other plants at the surface. The quantification and isolation of culturable nitrogen fixing bacteria were assessed. Also, phosphate solubilization capability and antagonism against Fusarium oxysporum were evaluated for the isolated strains. The strain genus identified with all capabilities mentioned above were Rhizobium, Bacillus, Pantoea, Paraburkholderia, Pseudomonas and Rhodococcus. El Carrizal showed the highest amount and ratio of nitrogen fixing bacteria strains with phosphate solubilization capability and antagonism against Fusarium oxysporum (11, out 82 isolated strains). Also, it was the area with the highest organic matter content (1.81%, average). The identification of rhizobacteria with multiple useful properties for agriculture is a major goal for sustainable development.